The Use of Modern Technologies in the Follow up of Cadet’s Formation in Football Schools - GHADBANE, Ahmed Hamza; BELGHOUL, Fathi; BRIKI, Tahar; KERFES, Nabil (Journal of Human Sciences, 2015)
We cannot deny that formation academies and schools of football are the responsible one for creating a generation of sport talents which support national teams and clubs. Recently, most countries were interested in making plans to develop team’s age stages through building up formation schools so as to realize a self – sufficiency in high level teams. In this intervention we will make an analytical study in which we concentrate on the importance of the use of modern technology in training and its role in the success of these schools. This is through the follow up of formation related to the preparation of modern training programs which are science – based. Indeed, these programs are conditioned with various age stages and the selection of specialized trainers in a scientific method. Because they know the characteristics of each age stage based on morphological, physiological, physical, skillful, psychological factors and of course through the use of technological means that give exact results in comparison with traditional methods, in order to form players according to scientific methods.